ANALISIS STUDI KOMPERATIF PERBANDINGAN KEY PERFORMANCE INDEX SWAP HUAWEI DENGAN NOKIA SIEMENS NETWORK PADA OPERATOR TELKOMSEL (STO TEBAS) - Jimmy . (Faculty of Engineering, Universitas Tanjungpura, 2015)
Abstract – The need for telecommunications is very important and makes the mobile operators including Telkomsel are trying ways to improvise their network system, by optimizing the BTSs one of way is to maintain and even increase the success call rate by optimizing the device by swapping Huawei BTS to Nokia Siemens Network (NSN) BTS. The results of the KPI comparison between the Huawei’s BTS with Nokia Siemens Network’s on the SDSR on Huawei BTS percentage of success rate is 99.59% raised calls is higher than the percentage of Nokia Siemens Network BTS by 98.49%, while the number of users who managed to raise the call on BTS Huawei is much less than of Nokia Siemens Networks BTS. As for Huawei BTS's HOSR successfull handover percentage rate of 98.91% is higher than the percentage of Nokia Siemens Networks BTS which is 94.95%, while the number of users who successfully handover on Huawei BTS is much less than the Nokia Siemens Networks BTS. TCH Blocking on Huawei BTS has a percentage rate of unsuccessful getting traffic channel of 1.09% higher than the percentage of Nokia Siemens Networks BTS by 0.01%, while the number of users who are not getting the traffic channel at Huawei BTS more than Nokia Siemens Networks BTS. In SD Blocking on Huawei BTS percentage rate unsuccessful getting SDCCH channel are the same as Nokia Siemens Networks BTS with the percentage of 0.00%, while the number of users who do not get on the SDCCH channel by Huawei BTS is much less than the Nokia Siemens Networks BTS. Drop Call on Huawei BTS has a highter percentage rate of unsuccessful calls to finish by 0.45% compared to the percentage of Nokia Siemens Networks BTS by 0,31%, while the number of users who fail to make a complete call on Huawei BTS is much less than the Nokia Siemens Network BTS. Keywords: Huawei, Nokia Siemens Networks, SDSR, HOSR, TCH Blocking, SD Blocking, Call Drop